KONSEP SOLIDARITAS ANTAR UMAT BERAGAMA DALAM PERSPEKTIF EMILE DURKHEIM - Zulfikar Falah (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2023)
This study analyzes the concept of inter-religious solidarity from the perspective of Emile Durkheim. The dictum regarding exclusive and inclusive teachings is under the auspices of every existing religion. Tension will arise when people of different religions show existential exclusivity of religion. Thus, solidarity becomes a way to neutralize tension. Emile Durkheim's solidarity theory is the result of interpretive ideas in interpreting the problematic relations of individuals with society. The formulation of the problem in this study is how is the concept of inter-religious solidarity from the perspective of Emile Durkheim. This study uses the library research method, with relevant sources, such as books, journals, theses, dissertations, etc. Responding to the formulation of the problem, this research gives the result that in Emile Durkheim's perspective, social change can occur due to the meaning of mechanical solidarity which turns into organic solidarity. This then implies that the relationship between religious communities with mechanical solidarity, social groups only see the importance of meeting the needs of facilities without having functional dependence. Harmony is increasingly intertwined in relations between religious communities with organic solidarity, harmony is increasingly intertwined, but it tends to promote functional dependence, and diversity is unstoppable.